The ideal type of valuer: expert, service provider or reporter? An investigation into prevailing role types in commercial valuation. Issue 2 (4th December 2020) - Klamer, Pim; Gruis, Vincent; Bakker, Cok
Abstract : Purpose: The purpose of this paper aims to disclose shared beliefs and understandings about the concept of professionalism amongst Dutch commercial real estate valuers. It examines prevailing logics of action in a mature European valuation industry and reflects on the potential influence of these logics on the occurrence of judgement bias in valuation. Design/methodology/approach: The underlying study adopted a grounded theory approach to facilitate reflexive in-depth interview sessions with 20 experienced valuation professionals in the Netherlands. Emerging data on core categories of professionalism were initially identified and grouped; and subsequently conceptualised into ideal role types of valuers using institutional logics theory. Findings: Three different ideal types appear to guide Dutch valuation practice: the expert, the service provider and the reporter. The expert emphasises professional standards and technical quality, while the service provider advocates commercial quality and the reporter aims to uphold procedural quality. The authors find that the attention for technical quality associated with the expert role may be at risk of underexposure, fostering concerns about judgement quality and associated bias risks. Research limitations/implications: The potential impact of both commercial and bureaucratic logics on valuation quality may raise authoritative and educational concerns over judgement bias effects. However, while trends in professionalism may transcend national boundaries, the specifics of local real estate market structures and regulations require replication of results in other markets. Originality/value: Institutional logics provide an alternative, socio-economic perspective on present-day valuer behaviour that progresses the understanding of the valuer–client relationship, thereby advancing the knowledge base on valuer judgement and client influence. Furthermore, the authors' role typology offers future research opportunities in terms of measurement and explanation of differences.